Pelatihan Penggunaan Microsoft Excel Untuk Pencatatan Laporan Keuangan Kepada Anggota/Karyawan KSP Bhakti Karya - Muhammad Muliadi; Saikin Saikin; Rizal Mahendra; Firmansyah Firmansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The financial sector is one area that is greatly influenced by the development of information technology. Both in administrative processes in financial institutions such as the Bhakti Karya savings and loan cooperative and non-formal training in the form of training outside financial institutions. Almost all financial institutions, companies, government agencies, financial institutions and others have switched to using electronic-based applications. The aim is to be able to process data easily and quickly. The Microsoft Excel training given to Ksp Karya Bhakti members/employees by the Community Service Team went smoothly. The institution welcomed this training activity because members/employees often feel overwhelmed when it is the end of the month to prepare the institution's financial reports. Especially members/employees in the reporting section who are still relatively new to using Microsoft Excel software in making institutional financial reports, so far making calculation reports has been done manually by writing in books and using a calculator.